The Role of GLUK5-Containing Kainate Receptors in Entorhinal Cortex Gamma Frequency Oscillations. (19th October 2008) - Stanger, Heather L.; Alford, Rebekah; Jane, David E.; Cunningham, Mark O.
Abstract : Using in vitro brain slices of hippocampus and cortex, neuronal oscillations in the frequency range of 30–80 Hz (gamma frequency oscillations) can be induced by a number of pharmacological manipulations. The most routinely used is the bath application of the broad-spectrum glutamate receptor agonist, kainic acid. In the hippocampus, work using transgenic kainate receptor knockout mice have revealed information about the specific subunit composition of the kainate receptor implicated in the generation and maintenance of the gamma frequency oscillation. However, there is a paucity of such detail regarding gamma frequency oscillation in the cortex. Using specific pharmacological agonists and antagonists for the kainate receptor, we have set out to examine the contribution of kainate receptor subtypes to gamma frequency oscillation in the entorhinal cortex. The findings presented demonstrate that in contrast to the hippocampus, kainate receptors containing theGLU K 5 subunit are critically important for the generation and maintenance of gamma frequency oscillation in the entorhinal cortex. Future work will concentrate on determining the exact nature of the cellular expression of kainate receptors in the entorhinal cortex.